Serelaxin, recombinant human relaxin-2, for heart failure patients: A systematic review and meta-analysis. Issue 25 (June 2018) - Yu, Ling; Cao, Lijuan; Sun, Jing; Li, Zhongyi; Yao, Fengzhen; Zhou, Yabin
Abstract: Background: Serelaxin, recombinant human relaxin-2, is a hormone with vasodilatory and end-organ protective effects. Recently, it has been licensed to treat acute decompensated heart failure. Here, a systematic review and meta-analysis on randomized controlled trials (RCTs) was performed to assess the effect of serelaxin on mortality and dyspnea improvement in patients with heart failure. Methods: RCTs comparing serelaxin treatment to other heart failure treatments were searched in PubMed, Embase, Cochrane Library, and ClinicalTrials.gov. The main endpoints were mortality and dyspnea improvement. Pooled data were assessed by using a random effects model. Results: A total of 451 studies were identified, of which 8 studies (8477 participants) were eligible and included in our analysis. Compared with other heart failure treatment group, serelaxin group had no effect on 30-day, 60-day, and 180-day mortality (OR, 0.79; 95% CI, 0.65–0.96). Compared with control group, there was no effect on dyspnea improvement. Conclusion: Serelaxin treatment is irrelevant with the mortality, and it cannot improve dyspnea of heart failure patients.